The public health role of the World Health Organisation through its postal record - Brabin , Bernard; Loretta, Brabin (Medicina Historica, 2024)
Founded in 1948, the World Health Organization (WHO) operated within the United Nations to address global public health issues. This paper examines whether philately was a successful strategy in helping WHO to influence health priorities and information needs in Member States. An historical basis for a postal strategy existed pre-1948 when health themes were used by the Red Cross and for Charity stamps. Initially (1948-1958) no specific public health stamps were issued but adoption of a WHO emblem promoted the organization’s reputation when included on postal stationary. From 1958 to 1978 stamps were notably issued for malaria programmes, smallpox eradication, child health, nutrition and vaccination. Member States released four billion stamps for the 1962 Malaria Eradication Programme omnibus issue while the popularity of the 1966 stamp showing, and inaugurating, WHO headquarters in Geneva legitimised its international status. WHO’s reputation was built on technical expertise as well as visual imagery, including photographs and postal stationary. Whether stamps raised health awareness as part of a multifaceted communication strategy could not be determined. Although Commemorative and World Health Day stamps continued to be issued in later decades, WHO shared the public – and political - health platform with other agencies. It lost its unique role in determining public health priorities and Member State stamp issues which are now generated for a multiplicity of topics. Postal revenues, rather than health messages, motivate Member States, such that stamps are no longer seminal to WHO’s role.